Intervensi Pengurangan Limbah Makanan dalam Program Makan Siang Sekolah: Tinjauan Sistematis dan Wawasan untuk Kebijakan Makan Siang Bergizi Gratis di Indonesia - Fahrani Husnun Nabila; Audya Titah Amalsha; Septiani Septiani; Dini Ririn Andrias (Universitas Airlangga, 2026)
Background: School meal programs generate substantial food waste. In addition to economic losses, food waste may reduce students’ nutritional intake, as uneaten food results in lower nutrient consumption. inappropriate portion sizes, limited meal times, and students’ food preferences. Objectives: This study aimed to assess whether the findings of food waste reduction interventions in school meal programs can inform the implementation of Indonesia’s Free Nutritious Meals policy. Methods: Authors electronically searched the PubMed and Scopus (2021–2025) databases for full-text articles on food waste reduction interventions in school meal programs using relevant keywords. Results: Five studies employing quasi-experimental and longitudinal methods, conducted in the United States, Spain, Sweden, Germany/Austria, and Singapore, met the specified criteria. Among the interventions, those involving regular plate waste monitoring and operational feedback were consistently associated with reductions in food waste, ranging from 6–44 g per serving and up to 17% overall. Behavioral education and awareness campaigns were able to reduce waste by approximately 30% in some cases, while choice architecture strategies, such as the Smarter Lunchrooms Movement, only brought about small but steady reductions of approximately 7%. Technological waste treatment showed substantial reductions in particular contexts, surpassing 40% in some schools, but mainly acted as a complementary strategy rather than a preventive strategy. In general, multi-component and data-driven approaches have achieved the best results. Conclusion: Portion control, food waste tracking, and student education are effective interventions for significantly reducing food waste in school feeding programs, this the main finding of this study. This study also provides the basis for considering that the Free Nutritious Meals policy in Indonesia may be strengthened by adopting similar strategies to promote efficiency and reduce food waste.